Clinical Evidence on Ayurvedic Interventions for Hypothyroidism and Subclinical Hypothyroidism: A Scoping Review - Aashish Patel; Suketha Kumari; Bawadkar Prasad (Journal of Ayurveda and Holistic Medicine (JAHM), 2026)
Background: Hypothyroidism is a prevalent endocrine disorder which has a significant clinical burden. The conventional levothyroxine therapy spans over a lifetime and symptoms may continue even after achieving biochemical remission. Ayurveda offers a holistic, integrative approach and can help overcome these limitations. Objectives: To systematically map existing evidence about the scope, range and type of clinical evidences Methods: Clinical studies conducted among adult persons (≥18 years) with hypothyroidism or subclinical hypothyroidism, evaluating any Ayurvedic intervention were eligible. Included study designs were randomized controlled trials (RCT’s), quasi-experimental studies, single-arm trial, and case reports with inclusion limited English language publications from January 2015 to December 2025. Medline (via PubMed), Scopus, Web of Science, Cochrane CENTRAL and Clinical trials registry of India. Final search was conducted on 31st December 2025. Data was collected using predefined and pilot tested charting form. Information on study characteristics, interventions, follow-ups studies duration and studies outcomes. Owing to heterogeneity of the included studies, findings were synthesized descriptively. Results: Fourteen studies were included: four RCT’s, three single-arm trials and seven case reports/series. Interventions comprise the use of single herbs, multi-herbal formulations, Herbo-mineral preparations, different Panchakarma procedures like Basti, and all-inclusive approaches combine diet and lifestyle management. Majority reported reduction in serum TSH levels apart from improvement in clinical symptoms, anthropometric parameters and quality of life. RCT’s provided comparatively better evidence mainly for all-inclusive approaches. Case-based evidence showed normalization of thyroid function and in one case, supervised withdrawal of levothyroxine. However, the studies were heterogeneous with several methodological constraints. Conclusions: Current clinical evidence suggests that Ayurveda interventions may have supportive role as adjuvant and integrative approach in hypothyroidism. Findings suggest consistent clinical benefits but several gaps exist. Well-designed, multi-centric RCTs involving standardized procedures and longer follow-ups are required to ascertain effectiveness and to increase generalizability.